Safety and side effect profile of Pfizer-BioNTech COVID-19 vaccination among healthcare workers: A tertiary hospital experience in Singapore - Lim, SM (Academy of Medicine, Singapore, 2021)
10.47102/annals-acadmedsg.2021160